Effect of male bud removal on the yield of Musa genotypes in a humid forest zone of West Africa - Okoro, J.; Vuylsteke, D.R.; Ortíz, R. (2000)
Plantains and bananas are economically important crops in many African countries where they are cultivated in compound gardens by small holders primarily for domestic consumption. These subsistence farmers generally believe that the cultural practice of removing the male buds from bearing banana plants soon after flower emergence, has beneficial effects on increasing the bunch weight and reducing the fruit filling period. To test this hypothesis, nine Musa genotypes comprising one triploid plantain landrace (Obino l'Ewai), six plantain derived tetraploid hybrids (TMPx), one tetraploid cooking banana hybrid (FHIA 3), and one triploid cooking banana cultivar (Cardaba) were evaluated. These genotypes are characterized by a persistent male bud at maturity. Male buds were removed at the point of transition from female to male flowers, at a stage one week after emergence of the last hand. The treated bunches of FHIA 3 were significantly heavier than untreated bunches. However, bunch weights of treated and untreated plants were not significantly different for the triploid cultivars and the TMPx hybrids. The number of days for fruit filling was not significantly reduced in any genotype irrespective of treatment. The results suggest that the practice of male bud removal has little or no beneficial effect on plantains grown in the West African humid environment. However, African farmers may consider removal of male buds for its food value as this is practiced in some parts of Asia